Administración pública y los principios del derecho administrativo en Perú - Rojas, Piero (2015)
The Draft Law on Peru’s Public Administration Framework is the first legal instrument that develops the fundamental standards of the organization and functioning of public administration. This piece seeks to reflect and provide critical commentary on how this bill deals legally with the concept of public administration and its main principles governing its operation.